2009
DOI: 10.1111/j.1524-4733.2008.00418.x
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Testing for Breast Cancer Susceptibility Genes

Abstract: The costs and effectiveness of both the test and no-test strategies are very similar even when there is a small probability of mutation. Current guidelines, which can be used by insurance companies to refuse coverage, could deny some women a cost-effective approach. Further research to decrease the frequency of inconclusive results could improve the cost-effectiveness of this test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
89
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(92 citation statements)
references
References 41 publications
0
89
0
3
Order By: Relevance
“…39 The identification of a pseudodeficiency mutation in the Tay-Sachs disease screening program foretold the occurrence of benign polymorphisms in other screening settings. 40 One advantage to ethnicity-based genetic screening is the comparatively low frequency of variants of uncertain significance (rare for Ashkenazi founder mutation testing versus 7% for comprehensive DNA sequencing 41 ).…”
Section: Effect Of Uncertain Variants On Cost-effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…39 The identification of a pseudodeficiency mutation in the Tay-Sachs disease screening program foretold the occurrence of benign polymorphisms in other screening settings. 40 One advantage to ethnicity-based genetic screening is the comparatively low frequency of variants of uncertain significance (rare for Ashkenazi founder mutation testing versus 7% for comprehensive DNA sequencing 41 ).…”
Section: Effect Of Uncertain Variants On Cost-effectivenessmentioning
confidence: 99%
“…One study suggested that genetic testing (i.e., comprehensive analysis at higher costs) was cost-effective even when the mutation detection probability was low, as long as a modest level of utility was gained from a negative result. 39 Of note, non-Jewish individuals volunteering for the Tay-Sachs screening program were offered testing. 40 …”
Section: A Translational Research Frameworkmentioning
confidence: 99%
“…Quadro 6. Busca eletrônica envolvendo estudos de avaliação econômica e mutação germinativa em genes BRCA1/2 (95)(96)(97)(98)(99)(100)(101)(102) . (97) , apesar da existência de diretrizes para a realização de testes genéticos em qualquer paciente com o diagnóstico comprovado de câncer de ovário.…”
Section: Paísunclassified
“…De todo modo, localizaram-se duas espécies de estudos que endereçaram temas pertinentes à mutação em genes BRCA1/2 na ausência de diagnóstico prévio de câncer de ovário. A primeira categoria de publicações avaliou a adoção de programa de rastreamento para mutação germinativa, em nível populacional, para indivíduos com algoritmo preditivo de risco para mutação ≥ 10% (99) ou etnia judaica Ashkenazi (95,98,102) . O segundo grupo de publicações avaliou a adoção de estratégias cirúrgicas preventivas para indivíduos reconhecidamente portadores de mutação germinativa em genes BRCA1/2 (88,92,93 Os objetivos do projeto principal relacionam-se ao reconhecimento do perfil genético de pacientes diagnosticadas com câncer de ovário, ao desenvolvimento de questionário para detecção de fatores associados, à estimativa de risco para mutação em genes BRCA1/2 mediante aplicação de algoritmos de risco e à avaliação de custoefetividade de testes genéticos.…”
Section: Paísunclassified
See 1 more Smart Citation